2005
DOI: 10.1161/01.cir.0000156457.35971.c8
|View full text |Cite|
|
Sign up to set email alerts
|

Platelet-Activating Factor Acetylhydrolase Activity Indicates Angiographic Coronary Artery Disease Independently of Systemic Inflammation and Other Risk Factors

Abstract: Background-Platelet-activating factor acetylhydrolase (PAF-AH), also denoted as lipoprotein-associated phospholipase A2, is a lipoprotein-bound enzyme that is possibly involved in inflammation and atherosclerosis. This study investigates the relationship of PAF-AH activity to angiographic coronary artery disease (CAD), the use of cardiovascular drugs, and other established risk factors. Methods and Results-PAF-AH activity, lipoproteins, sensitive C-reactive protein (sCRP), fibrinogen, serum amyloid A, and whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 38 publications
(35 reference statements)
7
67
0
Order By: Relevance
“…However, this mutation has not been found among Caucasians. 8 Among Caucasians, Lp-PLA2 was reported to be an independent risk factor for CAD and stroke in many, [9][10][11][12][13][14] but not all, studies. [15][16][17] Data assessing the relationship of CAC with Lp-PLA2 are very limited among Caucasians 18,19 and there are no data, to our knowledge, among the Japanese.…”
Section: Lp-pla2 and Coronary Calcificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this mutation has not been found among Caucasians. 8 Among Caucasians, Lp-PLA2 was reported to be an independent risk factor for CAD and stroke in many, [9][10][11][12][13][14] but not all, studies. [15][16][17] Data assessing the relationship of CAC with Lp-PLA2 are very limited among Caucasians 18,19 and there are no data, to our knowledge, among the Japanese.…”
Section: Lp-pla2 and Coronary Calcificationmentioning
confidence: 99%
“…[9][10][11][12][13][14] Whether Lp-PLA2 is an independent predictor of CAC or not is less clear. Only two studies examined the association between coronary calcification and Lp-PLA2 levels among white populations with inconsistent findings.…”
Section: Cac and Lp-pla2 Assessmentmentioning
confidence: 99%
“…28,29 The results of our multivariate analysis revealed that higher Lp-PLA2 levels were as powerful a predictor of coronary atherosclerosis as either LDL-C or HbA 1c . Thus, we postulate that the presence of atherosclerotic plaque could be evaluated by measuring circulating Lp-PLA2 concentrations.…”
Section: Discussionmentioning
confidence: 82%
“…An important issue is to determine whether to measure the mass of Lp-PLA 2 or to measure its enzyme activity. Several of the epidemiology studies measured only Lp-PLA 2 mass (2-5; 7-9; 15,16 ), whereas others measured only enzyme activity, (6,10,11,14 ) and a few have measured both in the same study population (12,13 ). The relatively low correlation (r ϭ 0.36) between Lp-PLA 2 mass and activity in recent studies has raised the question of precisely what is being measured with the respective assays (12 ).…”
Section: Lp-pla 2 Quo Vadis and Challenges Ahead?mentioning
confidence: 99%
“…These efforts have focused on 3 broad classes of biomarkers: (a) vascular imaging to identify the presence of atheroma or its composition; (b), functional assessments that reflect abnormal arterial homeostasis (e.g., arterial stiffness); and (c), measurements of soluble biomarkers. In recent years, several epidemiology studies have revealed an association between lipoprotein-associated phospholipase A 2 (Lp-PLA 2 )-a biomarker that may be viewed as a potential link between noxious effects of oxidized LDL cholesterol and elusive plaque vulnerability-and cardiovascular events (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Lp-PLA 2 , a member of phospholipase A 2 superfamily, is produced by inflammatory cells of myeloid origin, is associated with circulating atherogenic lipoproteins, and is highly expressed in the diseased vessel ( Fig.…”
mentioning
confidence: 99%